2015
DOI: 10.15585/mmwr.mm6436a1
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Coverage Among Health Care Personnel — United States, 2014–15 Influenza Season

Abstract: The Advisory Committee on Immunization Practices recommends annual influenza vaccination for all health care personnel (HCP) to reduce influenza-related morbidity and mortality among both HCP and their patients and to decrease absenteeism among HCP. To estimate influenza vaccination coverage among U.S. HCP for the 2014–15 influenza season, CDC conducted an opt-in Internet panel survey of 1,914 HCP during March 31–April 15, 2015. Overall, 77.3% of HCP survey participants reported receiving an influenza vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 5 publications
7
41
1
1
Order By: Relevance
“…Such activities support research in the United States of America (USA) (18), where the determinants of IV compliance among HCWs included occupational health encouragement, perceived importance of vaccination, on-site access, and no fear of adverse effects. Our findings agree with other studies, in which, among HCWs without an employer's obligation for vaccination, coverage was higher for HCWs in settings where vaccination was offered on-site at no cost for 1 (73.6%) or several (83.9%) days, and lowest among HCWs in settings where vaccination was not required, promoted or offered on site (44.0%) (19).…”
Section: Discussionsupporting
confidence: 91%
“…Such activities support research in the United States of America (USA) (18), where the determinants of IV compliance among HCWs included occupational health encouragement, perceived importance of vaccination, on-site access, and no fear of adverse effects. Our findings agree with other studies, in which, among HCWs without an employer's obligation for vaccination, coverage was higher for HCWs in settings where vaccination was offered on-site at no cost for 1 (73.6%) or several (83.9%) days, and lowest among HCWs in settings where vaccination was not required, promoted or offered on site (44.0%) (19).…”
Section: Discussionsupporting
confidence: 91%
“…27 Although there were no estimates available for the frequency of requirements or other policies for Tdap vaccination in LTC settings, requirements for and promotion of influenza vaccination have been reported to be less common in LTC settings compared with hospitals. 26 No increase in Tdap coverage was observed in LTC settings during the 3 years of the survey.…”
Section: Discussionmentioning
confidence: 90%
“…By occupational setting, the lowest coverage was observed among HCP working in LTC settings and the highest coverage was found among HCP working in hospitals for all 3 years, similar to patterns in influenza vaccination among HCP by occupational setting. 26 Higher coverage among HCP working in hospital settings could be attributable to policies requiring HCP to receive Tdap vaccination, such as making employment conditional upon receipt of Tdap vaccine for new employees and setting a termination date for noncompliance among current employees, policies that have been shown to increase vaccination levels. 14 Approximately 31% of U.S. hospitals had requirements for HCP to receive Tdap vaccine in 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Centers for Medicare and Medicaid Services (CMS) required hospitals to report HCP influenza vaccination levels as part of its hospital quality reporting programs in 2013 and the coverage results are publicly available, providing an incentive for hospitals to support employee vaccination. 32 The Internet panel survey also showed that influenza vaccination knowledge and awareness were higher among physicians and physician assistants/nurse practitioners compared with other HCP and among HCP working in hospital settings compared with those working in long-term care settings, indicating that vaccination knowledge and awareness among other clinical and non-clinical personnel and those working in long-term care settings could be further improved. 33 While the NHIS does not collect data on vaccination-related knowledge and attitudes or employer vaccination policies, the similar pattern of coverage estimates to those found in the Internet panel surveys suggest that vaccination policies including employee education along with free access to vaccination and other vaccine promotion could be effective in increasing influenza vaccination coverage, particularly among nursing, psychiatric, and home health aide staff and HCP working in long-term care settings.…”
Section: Discussionmentioning
confidence: 99%